Electrical discharge machining of ceramic nanocomposites: sublimation phenomena and adaptive control - Grigoriev, Sergey N.; Kozochkin, Mikhail P.; Porvatov, Artur N.; Volosova, Marina A.; Okunkova, Anna A. (Heliyon, 2019)
The productivity of electrical discharge machining (EDM) is relatively low owing to the natural laws of electrical erosion. Precise EDM demands uninterrupted control of the discharge gap and adjustment of process parameters. It is particularly critical for processing large workpieces with complex linear surfaces and for materials with threshold conductivities such as the new advanced ceramic nanocomposites Al2O3+TiC and Al2O3+SiCw+TiC(30–40%). In these cases, adequate flushing of erosion products is hampered by the geometry of the working space or by the small value of the required discharge gap, which does not exceed 2.2–2.5 μm. The methods of adaptive control in modern computer numerical control systems of EDM equipment based on measuring the electrical parameters in the working zone have been shown to be ineffective in the cases described above. This study aims to investigate the natural phenomena of material sublimation under discharge pulses for conductive ceramics and nanocomposites. The measured conductivities of the samples are higher than the percolation threshold. However, the question of machinability remains open owing to detected processing interruptions and poor quality of machined surfaces. New knowledge on EDM of conductive ceramics and nanocomposites can improve the final quality of the machined surfaces and productivity of the method by the introduction of advanced monitoring and control methods based on acoustic emissions. The manuscript presents an up-to-date overview and current state of the research on the subject area. The obtained morphology of the samples and discussion of the findings complete the experimental part of the study. The scientific basis for a new type of adaptive control system is provided. This can improve the effectiveness of parameter control for machining conductive ceramics and nanocomposites and contribute to an increase in the EDM performance for the most critical cases. Mechanical engineering; Metallurgical engineering; Nanotechnology; Materials science; Conductive ceramics; Wire tool; Discharge gap; Al2O3+SiCw+TiC; Al2O3+TiC; Sublimation; Vibrations; Acoustic emission; Monitoring